The effect of hotel lobby design on booking intentions: An intergenerational examination. (August 2020) - Nanu, Luana; Ali, Faizan; Berezina, Katerina; Cobanoglu, Cihan
Highlights: Examines the impact of hotel lobby design and biophilic design on the intention to book across different generations. The study uses the stimulus-organism-response (S-O-R) framework with the addition of Age as a mediator. Lobby interior design types have a significant impact on the booking intention among different generations. Millennials are impacted by the design type of the hotel lobby (contemporary vs. old) compared to non-millennials. Biophilic design has also been proven to impact the satisfaction and emotion of guests across all generations. Abstract: This paper aims to understand what elements of the hotel lobby design influence guest booking intentions. Lobbies are the first point of face-to-face communication between guests and staff upon arrival, impacting the initial guest perception of the property as well as playing an essential role in creating first impressions. Building on the Stimulus-Organism-Response framework, the study investigates preferences of millennial and non-millennial travelers towards hotel lobby design concerning style (contemporary vs. traditional) and biophilic elements (present vs. absent). This quantitative study is designed as an online, virtual, scenario-based experiment. The hypotheses were tested using MANOVA, ANOVA, and linear regression. The findings of the study reveal that the lobby interior design style has a significant impact on booking intention across different generations. Moreover, millennials are more impacted by the design style of the hotel lobby than non-millennials. Biophilic design has also been found to impact the satisfaction and emotions of guests across different generations.